2001
DOI: 10.1038/sj.onc.1204698
|View full text |Cite
|
Sign up to set email alerts
|

HACS1 encodes a novel SH3-SAM adaptor protein differentially expressed in normal and malignant hematopoietic cells

Abstract: SH3 and SAM domains are protein interaction motifs that are predominantly seen in signaling molecules, adaptors, and sca old proteins. We have identi®ed a novel family of putative adaptor genes that includes HACS1. HACS1 encodes a 441 amino acid protein that is di erentially expressed in hematopoietic cells and has restricted expression in human tissues. Its SH3 domain is most similar to the same motif in Crk and its SAM domain shares homology with a family of uncharacterized putative sca old and adaptor prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
68
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 18 publications
3
68
0
5
Order By: Relevance
“…SAMSN1 is mainly expressed by hematopoietic cells and mediates B-cell activation and differentiation. The SAMSN1 gene is located on chromosome 21q11-21, within a region associated with heterozygous deletions that is frequently present in lung cancer cells, suggesting that SAMSN1 acts as a tumor suppressor (13,14). This possibility is supported by (15), which revealed that SAMSN1 is a suppressor of multiple myeloma (15).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…SAMSN1 is mainly expressed by hematopoietic cells and mediates B-cell activation and differentiation. The SAMSN1 gene is located on chromosome 21q11-21, within a region associated with heterozygous deletions that is frequently present in lung cancer cells, suggesting that SAMSN1 acts as a tumor suppressor (13,14). This possibility is supported by (15), which revealed that SAMSN1 is a suppressor of multiple myeloma (15).…”
Section: Introductionsupporting
confidence: 56%
“…SAMSN1 is primarily expressed in human immune tissues as well as in cell lines and primary cells derived from patients with acute myeloid leukemia and multiple myeloma (15,37). In addition, SAMSN1 expression is upregulated by signaling factors that promote the activation and differentiation of B-cells (11,13). The present study hypothesized that chronic inflammation is caused by H. pylori infection-induced dysregulation of immune function and aberrant expression of SAMSN1 (38,39).…”
mentioning
confidence: 90%
“…In contrast, the adaptive immune system requires several days to get fully activated and to generate Ag-specific T cells that resolve the infection and provide a long-lasting immunity [10]. SLy1 (SH3-domain protein expressed in Lymphocytes 1) is exclusively expressed in lymphocytes and is part of a family of adapter proteins comprising three members, SLy1 [11], SLy2 [12], and SASH1 (SAM-and SH3-domain containing protein 1) [13]. SLy1 and SLy2 are highly homologous, as both express a bipartite nuclear localization sequence as well as an SH3 and an SAM domain [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…SLY1 is involved in regulation of the adaptive immune system (Beer et al, 2001(Beer et al, , 2005. HACS1 (or NASH1) is expressed in mast cells, and was reported to be differentially expressed in malignant haematopoietic cells (Claudio et al, 2001;Uchida et al, 2001;Zhu et al, 2004). Whereas the expression of SLY1 and HACS1 seems to be restricted to haematopoietic cells, SASH1 shows ubiquitous expression in human tissue (Zeller et al, 2003).…”
mentioning
confidence: 99%